Glossary: Medical Geography - Ruzaik, Fareena (Neptune Publications, 2020)
“Geography” is a multi-disciplinary subject, which has an interaction with human and environment. Opposite and unfavorable actions towards each of them will create negative impacts to the nature and living environment. This situation will cause health related issues to the mankind. The study of health issues in relation to the human and environment in the Geography is known as “Medical Geography”, which mainly focuses on spatial aspects of health care, health care planning and delivery, and health services. This has gradually become a crucial subject at present, due to the prevailing health risks to humans and the nature. Hence, the Department of Geography, University of Colombo understood the demands and has incorporated “Medical Geography and Applied Medical Geography” to its stream of study of special degree courses.
Keywords: Glossary; Geography; Medical